Economic Evaluation of the InTENSE Program of Therapy Alongside Botulinum Neurotoxin a for the Rehabilitation of Chronic Upper Limb Spasticity - Rachel Milte; Jia Song; Sean Docking; Julie Ratcliffe; Ian D. Cameron; Maria Crotty; Louise Ada; Coralie English; Natasha A. Lannin (Toxins, 2025)
Spasticity is a persistent and debilitating consequence of stroke and effective rehabilitation is a healthcare priority. Botulinum neurotoxin A (BoNT-A) with supportive therapy has increasingly been embedded within clinical practice for treatment of post-stroke spasticity. But the evidence for this approach has hitherto been limited to the findings of a limited number of small trials. The InTENSE trial was undertaken specifically to provide high-quality clinical trial evidence focusing on the effect of BoNT-A and adjunctive therapy on upper limb spasticity. While the clinical trial did not detect a significant impact upon clinical outcomes, there remains a need to evaluate any impact on the broader use of healthcare resources and overall cost-effectiveness. A detailed cost–utility analysis of the InTENSE trial was undertaken. The costs over the 12-month follow-up period were compared with quality-adjusted life years (QALY) gained using utilities generated from the EQ-5D three level (EQ-5D-3L) instrument. There were no significant differences in QALY gained between the intervention and control groups identified, or in the majority of health and community care costs. The Incremental Cost-Effectiveness Ratio per QALY gained was estimated at AU $63,947.11 (Australian dollars), which is well above accepted thresholds for cost-effectiveness in Australia. The study was unable to identify evidence for the cost-effectiveness of treatment approaches combining BoNT-A with adjunctive therapy.